ANALISIS PERBANDINGAN SISTEM PENGENDALIAN INTERN PERSEDIAAN BARANG DAGANG BERDASARKAN TEORI COSO PADA PT. MITRA ADIPERKASA TBK PERIODE AGUSTUS 2020-APRIL 2021 - Noviantika, Dara; Siswanti, Tutik (Jurnal Ilmiah Mahasiswa Akuntansi, 2023)
The purpose of this research is to determine the implementation of internal control, factors, and comparison of internal control of inventory at PT. Mitra Adiperkasa Tbk compared to COSO theory. Research data in the form of qualitative data with data sources from interviews with 25 respondents consisting of HRD Officer, Risk Officer, Warehouse Officer, Finance Officer, Accounting Officer, Purchasing Officer, Sales & Marketing Officer, Customer Service Officer, General Manager, Risk Officer , Finance & Accounting Manager, HRD Manager, and Warehouse Manager. Qualitative descriptive data analysis method. The results showed: (1) Implementation of control inventory using five components of internal control, elements of the Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring. (2) Factors that affect the internal control of inventory, Total Inventory, Human Resources, Documents, Standard Operating Procedures, and Audits. (3) Internal control of inventory that isn’t in accordance with COSO theory in the section on Sufficient Documents and Records, Information and Communication and Monitoring.